Do Changing Labor Market Conditions Affect the Length of Stay for Chronic Respiratory Failure Hospitalizations?. (November 2017) - Christensen, Eric W.; Maynard, Roy C.
The availability of home care nurses is widely seen as a cause for delayed discharge from inpatient care. However, there is a paucity of data to support or refute this hypothesis. If availability is driven by labor market conditions, the relative availability should vary over time with changing labor market conditions. The purpose of this study was to determine whether the length of stay for pediatric patients bound for home care was correlated with the local unemployment rate. We found that a 1-percentage-point (or marginal) increase in the unemployment rate was associated with a 2.3-day decrease in the length of stay for chronic respiratory failure hospitalizations. This suggests that labor market conditions result in delayed discharge for chronic respiratory failure patients.